A ratiometric near-infrared fluorescent probe based on a novel reactive cyanine platform for mitochondrial pH detection. Issue 25 (16th June 2021) - Wan, Shulin; Xia, Shuai; Medford, Jerry; Durocher, Emma; Steenwinkel, Tessa E.; Rule, Lexi; Zhang, Yibin; Luck, Rudy L.; Werner, Thomas; Liu, Haiying
Abstract : Near-infrared fluorescent probes for mitochondrial pH detection were prepared by a substitution reaction of chlorine atom of a near-infrared reactive cyanine platform (probe A) with amine derivatives. Abstract : A near-infrared reactive cyanine platform (probe A ) was prepared by condensation of 9-chloro-1, 2, 3, 4-tetrahydro-10-methyl-acridinium iodide with Fisher's aldehyde. A near-infrared fluorescent probe (probe B ) was prepared by modifying a reactive chlorine atom of probe A with tert -butyl(2-aminoethyl)carbamate through a substitution reaction. The deprotection of the Boc group of probe B was achieved under an acidic condition, affording an amine-functionalized cyanine dye (probe C ). A near-infrared ratiometric fluorescent probe (probe D ) for mitochondrial pH detection was synthesized by conjugating a FRET coumarin donor to a FRET cyanine acceptor (probe C ) through an amide bond connection. Probe A shows low fluorescence of 2% due to an electron-withdrawing chlorine atom, while probes B–D display high fluorescence quantum yields of 60%, 32%, and 35% in aqueous solutions containing 10% ethanol, respectively. Probes B–D show strong fluorescence with push–pull molecular structures in neutral and basic pH conditions. However, protonation of the probe's second amine at the 9-position under acidic condition disrupts the push–pull feature of the probes, resulting in fluorescence quenching of the new cyanine fluorophores. The probes can selectively stain mitochondria, while probe D was employed to detect pH changes in HeLa cells and Drosophila melanogaster first-instar larvae.